2019
DOI: 10.1111/jsr.12827
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dream rebound: evidence for emotion‐processing theories of dreaming

Abstract: Suppressing thoughts often leads to a “rebound” effect, both in waking cognition (thoughts) and in sleep cognition (dreams). Rebound may be influenced by the valence of the suppressed thought, but there is currently no research on the effects of valence on dream rebound. Further, the effects of dream rebound on subsequent emotional response to a suppressed thought have not been studied before. The present experiment aimed to investigate whether emotional valence of a suppressed thought affects dream rebound, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…This experiment explored whether a presleep-focused intrusive thought prompted people to report dreaming about that thought. Here, our external rating (rather than self-rating) found that participants in the suppression condition dreamed more of content that was related to their intrusive thoughts than participants in the control condition, in line with previous findings (Bryant et al, 2011; Malinowski et al, 2019; Taylor & Bryant, 2007). In addition, we found that participants in the expression condition dreamed more of content that was related to their intrusive thoughts than participants in the control condition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This experiment explored whether a presleep-focused intrusive thought prompted people to report dreaming about that thought. Here, our external rating (rather than self-rating) found that participants in the suppression condition dreamed more of content that was related to their intrusive thoughts than participants in the control condition, in line with previous findings (Bryant et al, 2011; Malinowski et al, 2019; Taylor & Bryant, 2007). In addition, we found that participants in the expression condition dreamed more of content that was related to their intrusive thoughts than participants in the control condition.…”
Section: Discussionsupporting
confidence: 92%
“…This kind of rating may minimize potential errors caused by situations stated earlier, and thus it was more suitable for a comparison between different conditions. Our rating result for the dream rebound effect may support our idea because, to our knowledge, most of the recent studies concerning the dream rebound effect adopted the external method to show their results (Bryant et al, 2011; Malinowski et al, 2019; Taylor & Bryant, 2007).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Within the field of dream research, several studies [ 12 , 13 , 14 , 15 ] have examined the so-called “dream rebound effect”: persons who are instructed to suppress specific thoughts prior to sleep onset are more likely to dream about it. Malinowski, Carr, Edwards, Ingarfill, and Pinto [ 15 ] were able to demonstrate that thought suppression of negatively toned thoughts showed an even stronger dream rebound effect, i.e., it occurred more often in dreams, than for the suppression of positive thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…Malinowski, Carr, Edwards, Ingarfill, and Pinto () present data from the field of dreaming. They follow the exciting theoretic assumption that especially dreaming during REM sleep may lead to a rebound of suppressed thoughts in dream content.…”
mentioning
confidence: 99%